Multiply Hölder functions - Rosas, Rudy (Pro Mathematica, 2024)
In this article we show several properties about multiply Hölder functions. We study the Hölder class of a composition of multiply Hölder functions and prove that a map and its inverse belong — under certain hypotheses — to the same Hölder class. We also prove some extension properties of multiply Hölder functions; for example, we show that a multiply Hölder functions always extends, in the same Hölder class, to “exceptional” sets that are codimension one manifolds.